Recognised the abilities of differently-abled persons - Abd Razak, Dzulkifli (2004)
At about the same time when the Caring Society Summit was launched by the Prime Minister, where he captured the hearts of a group of Universiti Sains Malaysia students, Ray Charles (19302004), the genius of "soul music" died (June 10). Like the group of students, Ray Charles ( www.raycharles.com ), would fondly be known as orang kelainan upaya, OKU for short, in the USM campus. The acronym OKU literally trans lates as "differentlyabled persons" who otherwise are commonly re ferred to as "disabled persons" or orang kurang upaya by society.